Resistensi Isolat Bakteri Asam Laktat dari Asinan Rebung Bambu Tabah (Gigantochloa nigrociliata Buse – Kurz) terhadap Antibiotik - Hutajulu, Irawaty Yolanda; Antara, Nyoman Semadi; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Probiotics are helpful bacteria that aid in the prevention and treatment of a variety of nutritional and health issues. Antibiotic overuse is a major contributor to the emergence of antibiotic-resistant pathogenic microorganisms. The goal of this study is to determine the level of antibiotic resistance of lactic acid bacteria isolates from pickled tabah bamboo shoots as a candidate for probiotic culture against the antibiotics amoxicillin, cefadroxil, and erythromycin, as well as the concentration level of antibiotic resistance. The diffusion method employed is paper disc diffusion. According to the research results, isolate PR.6.15.2 was resistant to erythromycin concentrations of 100 ppm (v/v), isolate PR.3.15.1 was resistant to concentrations of cefadroxil 100 ppm (v/v), erythromycin 100 ppm (v/v), and 200 ppm (v/v), with the diameter of the inhibition zone forming in a sequential order of 9.0 mm, 9.5 mm, 7.3 mm, and 8.8 mm. Keywords: bamboo shoots, tabah bamboo shoots, lactic acid bacteria, amoxicillin, erythromycin, cefadroxil